Erythroderma (exfoliative dermatitis). Part 2: energy homeostasis and dietetic management strategies. (1st August 2021) - Tso, S.; Moiz, H.; Satchwell, F.; Hari, T.; Dhariwal, S.; Barlow, R.; Forbat, E.; Blee, I. C.; Tan, Y. T.; Thind, C.; Ilchyshyn, A.; Randeva, H.; et al.
Summary: Erythroderma (exfoliative dermatitis) is associated with important metabolic changes that include an enhancement in energy expenditure. The key components to total energy expenditure (TEE) include basal metabolic rate ( 68% of TEE), physical activity ( 22% of TEE) and thermic effect of food ( 10% of TEE). In the erythrodermic state, there are likely multiple contributors to the increase in basal metabolic rate, such as 'caloric drain' resulting from increased evaporation of water from enhanced transepidermal water loss, increased activity of the cardiovascular system (including high‐output cardiac failure), increased nonshivering thermogenesis and hormonal changes such as hypercortisolaemia. A change in the patient's level of physical activity and appetite as a result of ill health status may further impact on their TEE and energy consumption. In Part 2 of this two‐part concise review, we explore the key constituents of energy homeostasis and the potential mechanisms influencing energy homeostasis in erythroderma, and suggest much‐needed dietetic management strategies for this important condition. Abstract : Click here for the corresponding questions to this CME article.